Perbaikan Teknologi Produksi Jamur Tiram dengan Variasi Waktu Perendaman Media Tumbuh Serbuk Kayu Gergaji - Sumiati, Ety; Djuariah, Dini (Indonesian Center for Horticulture Research and Development, 2005)
Substrat serbuk kayu gergaji harus bebas polutan dan mempunyai kadar air 65-70% untuk mendukung pertumbuhan optimal miselium dan hasil maksimal jamur tiram. Penelitian bertujuan untuk mendapatkan lama perendaman bahan baku serbuk kayu gergaji (SKG) yang optimal untuk perbaikan produksi bobot jamur tiram. Percobaan menggunakan rancangan petak terpisah dengan tiga ulangan. Petak utama adalah spesies jamur tiram, yaitu Pleurotus sayor-caju, P. flabellatus, P. cystuidiosus, P. ostreatus strain florida, dan P. pulmonarius strain sylvan 301. Anak petak yaitu waktu perendaman substrat SKG, yaitu 0, 3, 6, 9, dan 12 jam. Penelitian dilakukan di Balai Penelitian Tanaman Sayuran, Lembang, Jawa Barat. Hasil penelitian menunjukkan bahwa P. ostreatus strain florida dan P. sayor-caju masing-masing menghasilkan bobot jamur segar tertinggi (970,27 dan 942,26 g/kg substrat basah). Efisiensi biologis tertinggi berasal dari P. cystidiosus (48,84%) dan P. sayor-caju (43,74%) yang dibudidayakan pada substrat SKG yang direndam selama 12 jam.Â Improving oyster mushrooms production technology by dipping time variation of sawdust medium. Sawdust as main raw material of substrate must be free from pollutant with its water content of 65-70%, to obtain high yield of oyster mushrooms. The goal of this experiment was to gain the optimum dipping time of sawdust as growing media to improve oyster mushrooms yield. A split plot design was arranged with three replications. Main plot was oyster mushrooms species of Pleurotus sayor-caju, P. flabellatus, P. cystuidiosus, P. ostreatus strain florida, and P. pulmonarius strain sylvan 301. Subplot was dipping time of sawdust of 0, 3, 6, 9, and 12 hours, respectively. Research activities was carried out at Indonesian Vegetable Research Institute Lembang, West Jawa. Research results revealed that P. ostreatus strain florida and P. sayor-caju independently produced the highest yield, viz: 970.27 and 942.26 g/kg wet substrate. The highest values of biological efficiency were found from P. cystuidiosus (48.84%) and P. sayor-caju (43.74%) cultivated on the substrate with 12 hours dipping time. Sawdust must be dipped at least for 6 hours prior to set up substrate formula in order to catch sufficient water content (65-70%) for better growth of mycelium and finally produce high yield of oyster mushrooms.